POST-COLD WAR STATE INDUSTRIALIZATION AS A MEANS OF ECONOMIC GROWTH IN EAST ASIA VERSUS EASTERN EUROPE - James Tanoos (European Scientific Journal, ESJ, 2014)
The process of industrialization is often associated with an important time period in a nations‘s economic development as it shifts from small-scale agriculture to prosperity. Historically, the rise of the manufacturing sector in a country has foreshadowed subsequent growth and power, and many countries in Eastern Europe have seen these newfound opportunities to progress economically since the Cold War ended. Asian countries have similarly experienced newfound economic development because of the shift of production to underdeveloped areas along with the rise of outsourcing and offshoring in international manufacturing. While many studies have been conducted assessing the rise of industry as it relates to state and regional growth, comparative assessments of the contributions of the manufacturing sector to the economic rise among underdeveloped Asian nations as compared to Eastern European countries as a region have not been quantified. This study will analyze these two economically evolving areas in an effort to compare the overall economic growth since the fall of the Soviet empire as well as the extent to which that economic growth that can be attributed to the manufacturing sector. Trends in domestic manufacturing labor rates in these areas will also be assessed for this time period.